1993
DOI: 10.1093/glycob/3.6.609
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies raised against membrane glycoproteins from mouse brain recognize N-linked oligomannosidic glycans

Abstract: Monoclonal L3 and L4 antibodies have been shown to recognize carbohydrate epitopes on several neural cell adhesion molecules; these epitopes can be released by treatment with endoglycosidase H. In the present study, we have identified the oligosaccharides released by endoglycosidase H from the cell adhesion molecules AMOG and LI by fast-atom bombardment mass spectrometry as being solely of the oligomannosidic type. Using neoglycolipids of oligomannosidk glycans, we also report that both antibodies show the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Not only do both proteins harbor Ig-like domains, but a subset of these domains bear a striking resemblance in their sequence, an observation made previously [24],[25]. Interestingly, these very same Ig-like domains are capable of binding to membrane proteins carrying oligomannosidic N-glycans [26],[27],[28],[29]. The latter modification is only found on a relatively small number of mature N-glycosylated proteins expressed mainly in the brain, because oligomannose structures typically represent transient intermediates subject to additional posttranslational modification during their passage through the secretory pathway [26],[29],[30].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Not only do both proteins harbor Ig-like domains, but a subset of these domains bear a striking resemblance in their sequence, an observation made previously [24],[25]. Interestingly, these very same Ig-like domains are capable of binding to membrane proteins carrying oligomannosidic N-glycans [26],[27],[28],[29]. The latter modification is only found on a relatively small number of mature N-glycosylated proteins expressed mainly in the brain, because oligomannose structures typically represent transient intermediates subject to additional posttranslational modification during their passage through the secretory pathway [26],[29],[30].…”
Section: Resultsmentioning
confidence: 78%
“…Interestingly, these very same Ig-like domains are capable of binding to membrane proteins carrying oligomannosidic N-glycans [26],[27],[28],[29]. The latter modification is only found on a relatively small number of mature N-glycosylated proteins expressed mainly in the brain, because oligomannose structures typically represent transient intermediates subject to additional posttranslational modification during their passage through the secretory pathway [26],[29],[30]. Amongst the few known proteins carrying oligomannosidic N-glycan structures are the cell adhesion molecule L1, the β-subunit of the Na/K ATPase, the transferrin receptor, integrins [31] and members of the ectonucleotide pyrophosphatase/phosphodiesterase protein family [30].…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies and reagents. Rat monoclonal antibody A2D2 against mouse basigin (Heller et al, 2003), rat oligomannose-reactive monoclonal antibodies L3 and L4 (Schmitz et al, 1993), and rat monoclonal antibody 426 against adhesion molecule on glia (AMOG) (Antonicek et al, 1987) (mouse ␤2-ATPase subunit) were described previously. Polyclonal antibodies against basigin (also called EMMPRIN) (T-18), PrP (M-20), ␣2 Na ϩ /K ϩ -ATPase (C-16), and GluR2 (N-19) were purchased from Santa Cruz Biotechnology (Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore determined uptake of lactate in the presence of this monoclonal antibody. In addition, we tested antibodies against oligomannosidic glycans (Schmitz et al, 1993), a synthetic peptide that comprises the carbohydrate binding site within basigin (Heller et al, 2003) and purified oligomannosidic glycans. Interestingly, in all cases, uptake of lactate was increased ϳ1.5-fold (Fig.…”
Section: Basigin-mediated Lactate Uptake Depends On Oligomannosidic Gmentioning
confidence: 99%
“…Oligomannosidic glycans are transient on many glycoproteins early in the biosynthetic pathway and in most cases are subsequently remodeled to hybrid or complex oligosaccharides. However, experiments with antibodies that are specific for oligomannosidic moieties (Schmitz et al, 1993) have shown that glycoproteins expressing this type of glycan reach the cell surface. One example is the adhesion molecule on glia, which corresponds to the β2 subunit of Na + ,K + ‐ATPase, in which 80% of the carbohydrate is oligomannosidic and may mediate cis interactions that modulate the activity of this ion pump (Magyar et al, 1994).…”
Section: Discussionmentioning
confidence: 99%